Financial institutions, poverty and severity of poverty in Sub-Saharan Africa - Simplice Asongu; Valentine B. Soumtang; Ofeh M. Edoh (African Governance and Development Institute (AGDI), 2021)
The study assesses how financial institution dynamics have affected poverty and the severity of poverty in 42 sub-Saharan African countries for the period 1980-2019. In order to increase for policy relevance of the study, three financial development indicators are used, namely: financial institutions depth, financial institutions access and financial institutions efficiency. The adopted empirical strategy is a quantile regressions approach which enables the study to assess how financial institutions dynamics affect poverty and the severity of poverty throughout the conditional distribution of poverty and severity of poverty. The findings show various tendencies, inter alia: (i) financial institutions depth (efficiency) consistently decreases the severity of poverty (poverty headcount) and (ii) financial institutions access consistently decreases both poverty and the severity of poverty and the decreasing effect increases with increasing levels of poverty in the top quantiles and throughout the conditional distribution of the severity of poverty. Policy implications are discussed with respect of SDG1 on poverty reduction.
Keywords: G20; I10; I20; I30; O10; 330; financial development; poverty alleviation; Africa